2017
DOI: 10.1073/pnas.1619981114
|View full text |Cite
|
Sign up to set email alerts
|

Conformational dynamics of 1-deoxy- d -xylulose 5-phosphate synthase on ligand binding revealed by H/D exchange MS

Abstract: The enzyme 1-deoxy-d-xylulose 5-phosphate synthase (DXPS) is a key enzyme in the methylerythritol 4-phosphate pathway and is a target for the development of antibiotics, herbicides, and antimalarial drugs. DXPS catalyzes the formation of 1-deoxy-d-xylulose 5-phosphate (DXP), a branch point metabolite in isoprenoid biosynthesis, and is also used in the biosynthesis of thiamin (vitamin B) and pyridoxal (vitamin B). Previously, we found that DXPS is unique among the superfamily of thiamin diphosphate (ThDP)-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(96 citation statements)
references
References 38 publications
(59 reference statements)
5
91
0
Order By: Relevance
“…9A) suggesting that the PDZ domains may undergo only local conformational changes upon pSer 290 dephosphorylation. Consistent with previous observations in other proteins (64,65), and as illustrated in Fig. 9B (panels ii and iv), the regions exhibiting conformational changes upon pSer 290 dephosphorylation display a typical bimodal distribution of deuterium uptake as typified by the NHERF1 (39 -59) peptide.…”
Section: Structural Determinants Of Nherf1 Binding To Npt2a and Confosupporting
confidence: 91%
“…9A) suggesting that the PDZ domains may undergo only local conformational changes upon pSer 290 dephosphorylation. Consistent with previous observations in other proteins (64,65), and as illustrated in Fig. 9B (panels ii and iv), the regions exhibiting conformational changes upon pSer 290 dephosphorylation display a typical bimodal distribution of deuterium uptake as typified by the NHERF1 (39 -59) peptide.…”
Section: Structural Determinants Of Nherf1 Binding To Npt2a and Confosupporting
confidence: 91%
“…D-GAP or O 2 ) to trigger efficient LThDP decarboxylation on DXP synthase is established, the mechanism by which this occurs is not fully elucidated. Several mechanistic studies of DXP synthase have revealed compelling evidence for D-GAP-dependent conformational changes (12,16,17). For example, a recent HDX-MS study showed that a donor substrate analog and D-GAP induce closed and open conformations of DXP synthase, respectively (12).…”
Section: O 2 -Dependent Lthdp Decarboxylation On Dxp Synthasementioning
confidence: 99%
“…Several mechanistic studies of DXP synthase have revealed compelling evidence for D-GAP-dependent conformational changes (12,16,17). For example, a recent HDX-MS study showed that a donor substrate analog and D-GAP induce closed and open conformations of DXP synthase, respectively (12). It is conceivable that D-GAP binding induces a conformational change that destabilizes the LThDP intermediate, lowering the barrier for chemical decarboxylation of LThDP (12,15,16).…”
Section: O 2 -Dependent Lthdp Decarboxylation On Dxp Synthasementioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] Furthermore, the shapes of the isotopic distribution curves in HDX contain crucial information on the multiple conformations of a protein. [21][22][23] Consequently, a dedicated so ware program for the highly precise analysis of isotopic distribution would be expected to dramatically enhance investigations of the structural equilibrium between multiple protein conformations. ere is, however, no so ware currently available for analyzing the protein conformation and dynamics MALDI HDX MS data except for TOF2H.…”
Section: Introductionmentioning
confidence: 99%